Coexistence of Anal Atresia, Anophthalmia and Intestinal Neuronal Dysplasia Type-A in a Newborn - Hilal Aydin; Atilla Şenaylı; Fatih Mehmet Kışlal; Dilek Sarici; Burhan Köseoğlu; Servet Güreşçi (EL-Med-Pub, 2015)
We report a patient with anal atresia, anophthalmia and intestinal neuronal dysplasia type A.